The Changing Frequency of Celiac Disease Diagnosed at the Stollery Children’s Hospital - Seema Rajani; Hien Q Huynh; Justine Turner (Canadian Journal of Gastroenterology)
BACKGROUND: Celiac disease (CD) is recognized as one of the most common and important autoimmune gastrointestinal disorders affecting children. There is evidence that a diagnosis of CD during childhood improves health outcomes. The increasing prevalence of CD is due to increased awareness of the wide range of extraintestinal symptoms associated with CD.